Visual mislocalization during double-step saccades - Zimmermann, Eckart (Frontiers in Systems Neuroscience, 2015)
Visual objects presented briefly at the time of saccade onset appear compressed toward the saccade target. Compression strength depends on the presentation of a visual saccade target signal and is strongly reduced during the second saccade of a double-step saccade sequence (Zimmermann et al., 2014; 2014). Here, I tested whether perisaccadic compression is linked to saccade planning by contrasting two double-step paradigms. In the same-direction double-step paradigm, subjects were required to perform two rightward 10° saccades successively. At various times around execution of the saccade sequence a probe dot was briefly flashed. Subjects had to localize the position of the probe dot after they had completed both saccades. I found compression of visual space only at the time of the first but not at the time of the second saccade. In the reverse-direction paradigm, subjects performed first a rightward 10° saccade followed by a leftward 10° saccade back to initial fixation. In this paradigm compression was found in similar magnitude during both saccades. Analysis of the saccade parameters did not reveal indications of saccade sequence preplanning in this paradigm. I therefore conclude that saccade planning, rather than saccade execution factors, is involved in perisaccadic compression.